ENERGY GENERATOR PROTOTYPES DEVELOPMENT AND THESE RESEARCH INTEGRATION INTO THE EDUCATIONAL PROCESS - Matutis, Vaidotas; Savulioniene, Loreta; Sakalys, Paulius; Kasperavicius, Tomas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The paper presents the preconditions for improving the quality of technical training of engineers by integrating experimental research based on patented technology into the power supply circuits of autonomous robotic systems to improve power consumption and regeneration rate, ensuring longer autonomous robot operation. Not only the topics of arousal of curiosity in researching technical nuances are discussed, but also the promotion of motivation to delve into the study subjects envisaged in the curriculum and their integral understanding by examining the interrelationships. After-school activities are discussed: participation in the research, analysis of the research methodology, preparation of the layout for research and measurements; and the impact of these activities on the overall educational process. Suggestions for the integration of research results into the practical educational process of students are presented.